Analysis of the Meaning of the Word Bahr in the Qur’an: Toshihiko Izutsu's Semantic Perspective - Mustaqimah; Kharis Nugroho; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to examine the concept of the word "sea" in the Qur'an using a semantic approach according to Toshihiko Izutsu. Izutsu's profound semantic theory is applied to analyze this concept in order to gain a more comprehensive understanding of the meaning contained in "the sea." This research employs a qualitative approach involving the analysis of the content of the Qur'an. Although the Arabic word "البحر" (al-bahr) literally means "sea," its meaning is expanded to encompass spiritual, philosophical, and symbolic aspects. In several surahs, the word "البحر" is mentioned sixty times. This study demonstrates that the sea not only plays an important role in human life but also serves as a symbol of goodness, mercy, and divine power in creating and managing the universe. The sea also represents values such as tawakkul (trust in God), gratitude, and perseverance in the face of life's trials and tribulations. The study finds that the concept of "the sea" in the Qur'an is both complex and encompasses many metaphysical and physical meanings. Toshihiko Izutsu's exegesis reveals the truth of the Qur'an and its impact on knowledge, particularly in the field of oceanography; his semantic approach aids in understanding the depth of the word's meaning and provides deeper insights to readers regarding this phenomenon.